Eggshell appearance does not signal maternal corticosterone exposure in Japanese quail: an experimental study with brown-spotted eggs. - Camille Duval (Public Library of Science (PLoS), 2013)
Reproduction is a critical period for birds as they have to cope with many stressful events. One consequence of an acute exposure to stress is the release of corticosterone, the avian stress hormone. Prolonged stress can have negative impacts on the immune system, resulting in, for example, increased oxidative stress. Through maternal effects, females are known to modulate their investment in eggs content according to their own physiological condition. Less is known about maternal investment in eggshells, especially in pigments. The two main eggshell pigments may possess opposite antioxidant properties: protoporphyrin (brown) is a pro-oxidant, whereas biliverdin (blue-green) is an antioxidant. In Japanese quail, we know that the deposition of both pigments is related to female body condition. Thus, a chronic stress response may be reflected in eggshell coloration. Using female Japanese quails that lay brown-spotted eggs, we explored whether physiological exposure to corticosterone induces a change in female basal stress and antioxidant factors, and eggshell pigment concentration, spectrophotometric reflectance, and maculation coverage. We supplemented adult females over a 2 week period with either peanut oil (control) or corticosterone (treatment). We collected pre- and post-supplementation eggs and analysed the effect of corticosterone treatment on female physiology and eggshell appearance parameters. Except for corticosterone-fed birds which laid eggs with brighter spots, supplementation had no significant effect on female physiology or eggshell pigment concentration, reflectance and maculation. The change in eggshell spot brightness was not detected by a photoreceptor noise-limited color opponent model of avian visual perception. Our data confirms that eggshell reflectance in spotted eggs varies over the laying sequence, and spot reflectance may be a key factor that is affected by females CORT exposure, even if the changes are not detected by an avian visual model.